Clinician's experience of telepsychiatry consultations with elderly patients - Chandrima Naskar; Sandeep Grover; Aseem Mehra; Swapnajeet Sahoo (Journal of Geriatric Mental Health, 2022)
Background: During the coronavirus disease-2019 pandemic, telepsychiatry became a norm as a primary method of health-care delivery across India. However, not much evidence is available regarding the experience of psychiatrists in providing a telepsychiatry consultation. Objective: This study aims to assess the experience and satisfaction of the clinician in providing teleconsultations to elderly patients/their caregivers. Methodology: Clinicians scored their experience, satisfaction, and their perception of therapeutic alliance in providing the teleconsultation to patients of age 60 years or more, in a detailed Google Forms-based questionnaire. Results: Ninety-eight teleconsultations were assessed by clinicians. The patients had a mean age of 69.5 years, with an equal number of males and females. In more than 80% of the teleconsultations, patients were accompanied by their relatives. In about one-fourth of the consultations, psychiatrists encountered connectivity issues from the patient side. Overall, for three-fourth (72%) of the teleconsultations, clinicians reported being satisfied to a large extent; for two-thirds (66%) of the consultations, the clinicians rated their teleconsultation experience as that of providing an in-person consultation; and for about 10% of consultations, the experience was rated as better than the in-person consultation. In terms of a therapeutic alliance, in almost 85%–90% of consultations, the clinicians noted that they could build a rapport, empathize with their patients, and build a relationship of trust with the patients and their caregivers. Conclusions: Teleconsultation with the elderly might not be as difficult as intuitively thought and clinicians are in general satisfied with the same and consider that they can establish a good therapeutic alliance with the patients and their caregivers.